2018
DOI: 10.1007/s10815-018-1246-x
|View full text |Cite|
|
Sign up to set email alerts
|

Contraction behaviour reduces embryo competence in high-quality euploid blastocysts

Abstract: Most aneuploid blastocysts diagnosed by PGT-A have complex aneuploidies, showing that aneuploid embryos can develop after genomic activation and reaching high morphological scores. It becomes clear that embryo contraction, despite being a physiological feature during blastulation, is conditioned by the ploidy status of the embryo. Furthermore, the presence of contractions may compromise implantation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…Moreover, in agreement with our study, a reduction in the pregnancy rate was reported if blastocysts that displayed a collapse episode were transferred, compared to the non-collapse group (47.6% versus 78.5%, respectively). Although this is the first study to report such data, it might be clear that spontaneously blastocyst collapse, despite being a physiological feature during blastulation, is conditioned by the ploidy status of the embryo (Viñals Gonzalez et al, 2018). In conclusion, the analysis of spontaneous blastocyst collapse could be used as tool to improve embryo selection, especially when there are several blastocysts available for transfer.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, in agreement with our study, a reduction in the pregnancy rate was reported if blastocysts that displayed a collapse episode were transferred, compared to the non-collapse group (47.6% versus 78.5%, respectively). Although this is the first study to report such data, it might be clear that spontaneously blastocyst collapse, despite being a physiological feature during blastulation, is conditioned by the ploidy status of the embryo (Viñals Gonzalez et al, 2018). In conclusion, the analysis of spontaneous blastocyst collapse could be used as tool to improve embryo selection, especially when there are several blastocysts available for transfer.…”
Section: Discussionmentioning
confidence: 85%
“…Although in the present study we did not perform any pre-implantation genetic screening, the chromosomal abnormalities could perhaps clarify the difference in clinical outcomes between the two groups (collapse and not collapse). A recent study published by Viñals Gonzalez et al (2018) investigates the correlation between blastocyst collapse patterns and genetic complements in human embryos. Eight hundred ninety-six good quality blastocysts were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…However, still the most widely used selection protocol is a subjective, single point morphological assessment of the embryo before transfer. More recently, the introduction of time-lapse imaging has been importantly instructive; objectively demonstrating a high incidence of morphological dysmorphism during cleavage, concomitant with reduced implantation and live births, providing sophisticated morphokinetic computations as a prognosticator for embryo viability (Campbell and Fishel, 2015;Lagalla et al, 2016;Pribenszky et al, 2017;Reignier et al, 2018;Viñals Gonzalez et al, 2018;Zhan et al, 2016), and introducing machine learning to evolve independent selective algorithms for automated programming (Kohsravi et al, 2019;Tran et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the presence of contractions may compromise the implantation rates. [ 15 ] Taken altogether, maternal age and some morphological parameters (expansion, time of blastocyst formation, and trophectoderm grade) were associated with euploidy, whereas other parameters, such as embryo sex and biopsy day, were not related to aneuploidy. There was a positive correlation between the speed of D4 embryo development and the time of blastocyst formation.…”
Section: Discussionmentioning
confidence: 99%